Simulação computacional por dinâmica molecular de filmes finos orgânicos irradiados por íons pesados : comparação entre o potencial FENE e Lennard-Jones - Lima, Nathan Willig (2016)
In this work, molecular dynamics simulations of thin organic films irradiated by fast heavy ions were implemented. In order to represent the ion energy deposition, it was used a Thermal Spike Model, in which the ion track is represented as a cylindrical region with high temperature. Two papers were submitted for publication based on this study. In the first paper, it was studied the impact of film thickness and the ion energy in the topological effects of radiation (such as crater diameter, crater depth and rim volume) and in the sputtering, comparing the results for a crystalline and amorphous solids modeled by the Lennard-Jones potential. In the second paper, the FENE potential was implemented to build samples with molecular chains. The ionic radiation effects were then compared between films with molecular chains (modeled by the FENE potential) and without molecular chains (using the Lennard-Jones potential). In both works, the effects of radiation were explained by analyzing the different mechanisms of energy dissipation: evaporation, melt flow and plastic deformation. Our results show that radiation effects are strongly determined by film thickness. The simulations with FENE potential show that the presence of molecular chains reduces significantly the effects of radiation. In solids thinner than the mean gyration radius of the sample, there was not any radiation effect, indicating that the effect reduction is related not only to the decreasing of mobility but also to molecular conformation and entanglement.